Putting Nigeria to Work : A Strategy for Employment and Growth - Treichel, Volker (World Bank, 2012)
The goal of this book is to shed light on the extent to which Nigeria's much improved economic performance has impacted the labor market, and to develop a growth strategy that can enhance the employment intensity of growth. The report consists of six chapters. Chapter one provides an overview of the book's main findings, reviews Nigeria's growth performance from 2001 to 2007, and addresses the question of the sustainability of that growth performance. Chapter two analyzes the evolution of the labor market since 1999. The analysis focuses on the share of the formal and informal sectors in employment, the trend in incomes in the formal and the informal sectors, and the unemployment rate. Chapter three addresses the question of what Nigeria can do to increase the availability of quality jobs and reduce rising youth unemployment. Chapter four discusses Nigeria's industrial policy and investment environment. Chapter five proposes strategies for skills development; and chapter six analyzes the effects of restrictive trade policies.